THE CONNECTOR “BUT”: GRAMMAR AND SITUATIO NAL CONTEXT - Ochoa, Jasmin (2012)
This paper analyzes the different meanings of the connector but in differentcommunicative situations. It also verifies its applicability in Peruvian short-storieswritten by different authors. It is known that grammar deals with the study ofthis connector semantically as a contradiction, i.e., that it joins two propositions ofopposing ideas. Besides, grammar analyzes it as a restrictive connector. However,in various real situations it assumes varied meanings that have not been properlystudied by grammar yet.